2015
DOI: 10.1007/s13197-015-1918-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phytic acid on nutrient bioaccessibility and antioxidant properties of dehusked rice

Abstract: Whole grains consumption promotes health benefits, but demonstrates controversial impacts from phytic acid in meeting requirements of good health. Therefore, this study was aimed to determine the nutrient bioaccessibility and antioxidant properties of rice cultivars named "Adan" or "Bario" and deduce the nutritional impact of phytic acid. Majority of the dehusked rice in the collection showed an acceptable level of in-vitro starch digestibility and in-vitro protein digestibility, but were poor in antioxidant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…After milling, the PA content was reduced up to 85%, while percent reduction was 58 and 80 in Bindli and PB267, respectively (Figure b). Lee, Loh, Bong, Sarbini, and Yiu () reported similar range of PA (0.826–3.235 g/100 g) in rice genotypes. Major amount of PA is present in the aleurone layer and can be removed by milling process (Itani, Tamaki, Arai, & Horino, ).…”
Section: Resultsmentioning
confidence: 79%
“…After milling, the PA content was reduced up to 85%, while percent reduction was 58 and 80 in Bindli and PB267, respectively (Figure b). Lee, Loh, Bong, Sarbini, and Yiu () reported similar range of PA (0.826–3.235 g/100 g) in rice genotypes. Major amount of PA is present in the aleurone layer and can be removed by milling process (Itani, Tamaki, Arai, & Horino, ).…”
Section: Resultsmentioning
confidence: 79%
“…These results might be explained by the fact that minerals and phytate are not always found in the same part of the seeds or grains and that phytate can be linked to other elements such as magnesium or potassium or the variability of phytate depending of the maturity of the seeds or grains (Reddy & Sathe, ). Lee, Loh, Bong, Sarbini, and Yiu () reported no correlation between phytate and minerals in a study carried out with 30 samples of two rice cultivars from Malaysia. Masum Akond, Crawford, Berthold, Talukder, and Hossain () reported a negative correlation for phytate and iron, and calcium, and between phytate and zinc in 29 common bean genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…This include sesame (39.3–57.2 mg/g), soyabeans (12.2–19.3 mg/g), maize (9.8–21.3 mg/g), peanuts (9.2–19.7 mg/g), buckwheat (9.2–16.2 mg/g), rice (1.2–3.7 mg/g), wheat (1.1–3.3 mg/g) (Bilyeu et al, ; Greiner & Konietzny, ; Kim, Mullan, Selle, & Pluske, ). The relationship between phytic acid content and mineral bioavailability was investigated in rice by Lee, Loh, Bong, Sarbini, and Yiu (). They observed that phytic acid significantly impaired the mineral bio accessibility and contribute to antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…(1.1-3.3 mg/g) (Bilyeu et al, 2008;Greiner & Konietzny, 2006;Kim, Mullan, Selle, & Pluske, 2002). The relationship between phytic acid content and mineral bioavailability was investigated in rice by Lee, Loh, Bong, Sarbini, and Yiu (2015). They observed that phytic acid significantly impaired the mineral bio accessibility and contribute to antioxidant properties.…”
Section: Phytic Acid Contentmentioning
confidence: 99%